Programmable data processing method and system design for polymorphic network - Jinlin WANG; Li’nan JING; Xiao CHEN; Jiali YOU (Tongxin xuebao)
Aiming at the problems of compatible with multiple route identification, network protocols and network application data processing faced by multimodal networks, a programmable data processing method compatible with multiple modes was proposed.Through the mode recognition and classify module to identify packets of different network modes, the data type, offset and length were used to represent multiple types of data, and the modal data processing pipeline was formed by using the matching action data table with selectable matching algorithm and processing action to process data of different types of network.A prototype system for data processing of polymorphic network was implemented and verified by using the proposed method.Experimental results show that the modal data processing pipeline can isolate the network of different modes and ensure the performance independence, the type of matching algorithm and the length of the processed data will affect the forwarding performance of the system, while the type of data will not.